The implication of next-generation sequencing in the diagnosis and clinical management of non-Hodgkin lymphomas - Tomacinschii, Victor; Mosquera Orgueira, Adrian; Santos, Carlos Aliste; Robu, Maria; Buruiana, Sanda; Fraga Rodriguez, Maximo Francisco (Frontiers in Oncology, 2023)
Next generation sequencing (NGS) is a technology that broadens the horizon of knowledge of several somatic pathologies, especially in oncological and oncohematological pathology. In the case of NHL, the understanding of the mechanisms of tumorigenesis, tumor proliferation and the identification of genetic markers specific to different lymphoma subtypes led to more accurate classification and diagnosis.Similarly, the data obtained through NGS allowed the identification of recurrent somatic mutations that can serve as therapeutic targets that can be inhibited and thus reducing the rate of resistant cases. The article's purpose is to offer a comprehensive overview of the best ways of integrating of next-generation sequencing technologies for diagnosis, prognosis, classification, and selection of optimal therapy from the perspective of tailor-made medicine.